Orpheão Rio Grandense (1930-1952): vinte e dois anos na vida cultural de Porto Alegre - Kênia Simone Werner (2019)
This thesis tells the trajectory of Orpheão Rio Grandense, a singing society created in 1930 that,for twenty-two years,had an active participation in the cultural life of Porto Alegre. It staged operas, promoted concerts and lead some daring initiatives, like the creation of an orchestra, a magazine and a lyric school. The objective of this work is to identify the musical and social universe of Orpheão Rio Grandense through its practices in the environments where it acted. For that, it will be analysed how this institution and its practices inserted themselves in the scenery of Porto Alegre and what circumstances and factors sustained its tewnty-two years of existence and caused its decadence. The data were collected essentially from periodicals of that time, such as Correio do Povo newspaper, which disclosure of events and critics published in it were essential for the unveiling of the story. Due to its peculiarities and variation of activities, several authors are reffered, giving spotlight to Haward Becker and the concept of "Art Worlds", being the activities of Orpheão analysed as collective actions.